Survey Satisficing Inflates Stereotypical Responses in Online Experiment: The Case of Immigration Study - Miura, Asako; Kobayashi, Tetsuro (Frontiers in Psychology, 2016)
Though survey satisficing, grudging cognitive efforts required to provide optimal answers in the survey response process, poses a serious threat to the validity of online experiments, a detailed explanation of the mechanism has yet to be established. Focusing on attitudes toward immigrants, we examined the mechanism by which survey satisficing distorts treatment effect estimates in online experiments. We hypothesized that satisficers would display more stereotypical responses than non-satisficers would when presented with stereotype-disconfirming information about an immigrant. Results of two experiments largely supported our hypotheses. Satisficers, whom we identified through an instructional manipulation check (IMC), processed information about immigrants’ personality traits congruently with the stereotype activated by information provided about nationality. The significantly shorter vignette reading time of satisficers corroborates their time-efficient impression formation based on stereotyping. However, the shallow information processing of satisficers can be rectified by alerting them to their inattentiveness through use of a repeated IMC.